Pengaruh Pengetahuan Investasi, Literasi Ekonomi Syariah dan Persepsi Risiko Dalam Pengambilan Keputusan Berinvestasi di Pasar Modal Syariah (Studi Empiris pada Mahasiswa Akuntansi di Kota Malang) - Devi Ardhelia; Nur Diana; Junaidi Junaidi (e_Jurnal Ilmiah Riset Akuntansi, 2023)
This research intends to ascertain how investing knowledge, islamic economic literacy and risk perception on investment decision making in the Islamic capital market. This research uses primary data with the criteria of students of the undergraduate accounting students from the 2019 classes of the Islamic University of Malang, state University of Malang and University of Merdeka Malang participated in this quantitative survey. Data collection in this study used a questionnaire using the Google Form with a Likert scale of 1-5. The number of samles used in this study was 248 students, with a data analysis method of multiple linear regression analysis. The result of the research test prove that the investment knowledge, islamic economic literacy and risk perception had a positive effect on investment decision making in the islamic capital market.Keywords: Investment knowledge, islamic economic literacy, risk perception, investment decision.